Glyphosate‐resistant Italian ryegrass (Lolium multiflorum) on rice paddy levees in Japan. Issue 1 (6th March 2013) - Niinomi, Yuki; Ikeda, Mutsuhiro; Yamashita, Masayuki; Ishida, Yoshiki; Asai, Motoaki; Shimono, Yoshiko; Tominaga, Tohru; Sawada, Hitoshi
<x xml:space="preserve">Abstract</x> The rapid range expansion of naturalized Italian ryegrass (Lolium multiflorum Lam.) in farmland is a serious problem in Fukuroi city in Shizuoka Prefecture, Japan. Glyphosate has been used to control Italian ryegrass in the levees of rice paddy fields and wheat fields for ∼20 years, but this weed in Fukuroi city is poorly controlled by glyphosate. In order to elucidate the level of resistance to glyphosate in Italian ryegrass populations, seed bioassays and a foliar application experiment, using seeds collected from 16 wild populations in and around Fukuroi city and from three susceptible cultivars, were conducted. For the susceptible cultivars and one population from a site where glyphosate had not been applied for >10 years, the shoot length in the seed bioassays was greatly suppressed at a glyphosate concentration of 10 mg ai L−1 and no seedling survived after the foliar application of glyphosate at a rate of 2.3 kg ai ha−1. Nine wild populations from levees in the southern part of Fukuroi city showed vigorous shoot growth at a glyphosate concentration of 10 mg ai L−1 and had at least a 78% survival rate after the application of glyphosate at 2.3 kg ai ha−1. Four wild populations from levees in the northern part of Fukuroi city showed a slight suppression of the shoot growth as a result of the glyphosate treatment and their survival rates ranged from 20 to 64%. The results suggested that resistance to glyphosate has evolved in the wild populations of Italian ryegrass that are growing on the levees. This is the first report of a glyphosate‐resistant weed in Japan.